2015
DOI: 10.3390/s150612498
|View full text |Cite
|
Sign up to set email alerts
|

Impedance of the Grape Berry Cuticle as a Novel Phenotypic Trait to Estimate Resistance to Botrytis Cinerea

Abstract: Warm and moist weather conditions during berry ripening provoke Botrytis cinerea (B. cinerea) causing notable bunch rot on susceptible grapevines with the effect of reduced yield and wine quality. Resistance donors of genetic loci to increase B. cinerea resistance are widely unknown. Promising traits of resistance are represented by physical features like the thickness and permeability of the grape berry cuticle. Sensor-based phenotyping methods or genetic markers are rare for such traits. In the present study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
49
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(53 citation statements)
references
References 21 publications
3
49
0
1
Order By: Relevance
“…In contrast, cuticle and wax content, as well as the number and thickness of epi-and hypodermal cell layers were weakly positively correlated with resistance. This is consistent with later work that found Botrytis resistance to be associated with thicker skins and high levels of epicuticular waxes, both of which are undesirable characteristics for commercial cultivars (Deytieux-Belleau et al, 2009;Herzog et al, 2015). Other evidence has suggested that aromatic volatiles produced by V. labrusca accessions reduce pathogenicity and spore production of B. cinerea (Kulakiotu et al, 2004).…”
supporting
confidence: 90%
See 1 more Smart Citation
“…In contrast, cuticle and wax content, as well as the number and thickness of epi-and hypodermal cell layers were weakly positively correlated with resistance. This is consistent with later work that found Botrytis resistance to be associated with thicker skins and high levels of epicuticular waxes, both of which are undesirable characteristics for commercial cultivars (Deytieux-Belleau et al, 2009;Herzog et al, 2015). Other evidence has suggested that aromatic volatiles produced by V. labrusca accessions reduce pathogenicity and spore production of B. cinerea (Kulakiotu et al, 2004).…”
supporting
confidence: 90%
“…Studies have evaluated physical, chemical, morphological, and genetic components contributing to Botrytis resistance in Vitis (Deytieux-Belleau et al, 2009;Gabler et al, 2003;Herzog et al, 2015;Kulakiotu et al, 2004;Renault et al, 2000;Trotel-Aziz et al, 2006). Gabler et al (2003) determined that the number of surface pores on berries was negatively correlated with resistance.…”
mentioning
confidence: 99%
“…These factors include thin berry cuticles (Comménil et al, 1997;Zoffoli et al, 2009), low epicuticular wax content (Marois et al, 1986Percival et al, 1993), high berry porosity (Blaich et al, 1984;Mlikota Gabler et al, 2003), and the number and thickness of the skin cell layers of the berry (Mlikota Gabler et al, 2003). A sensor that enables the measurement of the electrical impedance of the grape berry cuticles and their epicuticular waxes has been developed as a reliable method to estimate the degree of berry susceptibility to GM and could be a valuable tool for genetic analysis in breeding programs (Herzog et al, 2015).…”
Section: Genetic Factorsmentioning
confidence: 99%
“…Botrytis infestation then reduces grape yield and the quality of wines due to off-flavors or reduced wine stability in susceptible grapevine cultivars [1]. Besides climatic conditions, susceptibility of grapes against Botrytis bunch rot is mainly influenced by morphological properties like the bunch compactness, canopy structure as well as the thickness of the berry skin and hydrophobic characteristics of the berry cuticle ( [2], [3], [4], [5], [6]). The cuticle and its epicuticular wax layer hereby represents the outer layer of the grapevine berries (cf.…”
Section: Introductionmentioning
confidence: 99%
“…Laborious phenotyping methods are not feasible in grapevine research and breeding where berries of several hundreds of genotypes have to be evaluated in a short time. Regarding objective and highthroughput phenotyping techniques, Herzog et al [6] developed a sensor-based method in order to characterize the thickness and permeability of grape berry cuticles by measuring the electrical impedance. High impedance is described as an indicator for thick berry cuticle and berry bloom [6].…”
Section: Introductionmentioning
confidence: 99%